Ancient Borinquen : archaeology and ethnohistory of native Puerto Rico - Siegel, Peter E. (Book collections on Project MUSE., 2005)
Native American cultures of Puerto Rico prior to the arrival of the Spanish in 1493.A book on the prehistory of a modern geopolitical entity is artificial. It is unlikely that prehistoric occupants recognized the same boundaries and responded to the same political forces that operated in the formation of current nations, states, or cities. Yet, archaeologists traditionally have produced such volumes and they generally represent anchors for ongoing research in a specific region, in this case the island of Puerto Rico, its immediate neighbors, and the wider Caribbean basin. To varying degrees, t.